2008
DOI: 10.1002/adma.200801460
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Ultrathin Single‐Crystal Diamond Membranes

Abstract: The extreme properties of diamond have led its use in a wide variety of applications from drilling for oil to ultra sharp knives for eye surgery. In the nanotechnology realm, diamond is being recognized as a material with great potential. For example, the extremely high modulus suggests that diamond could be used in Nano-Electro-Mechanical systems (NEMS) and quantum NEMS applications since diamond cantilevers will have higher oscillation frequencies than other materials. Furthermore diamond is chemically inert… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
84
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(85 citation statements)
references
References 68 publications
1
84
0
Order By: Relevance
“…However, a major challenge to achieving diamond-based quantum photonics is the difficulty in processing single-crystal diamond for the fabrication of optical cavities coupled to its color centers. Indeed, fabricating such cavities from bulk single crystal diamond by ion implantation degrades the optical properties of the embedded color centers impeding their use for photonic platforms [18,19]. Furthermore, earlier work has shown that using nanocrystalline diamond to form optical cavities places limits on the quality factors of those cavities [20].…”
Section: (B)mentioning
confidence: 99%
“…However, a major challenge to achieving diamond-based quantum photonics is the difficulty in processing single-crystal diamond for the fabrication of optical cavities coupled to its color centers. Indeed, fabricating such cavities from bulk single crystal diamond by ion implantation degrades the optical properties of the embedded color centers impeding their use for photonic platforms [18,19]. Furthermore, earlier work has shown that using nanocrystalline diamond to form optical cavities places limits on the quality factors of those cavities [20].…”
Section: (B)mentioning
confidence: 99%
“…During this process, the lattice damage induced by the stopping of fast ions is used to generate a buried graphite layer that can be etched away to lift of a thin diamond membrane. The original idea was incepted by Parikh in the late 90s [126] , however, only several years ago diamond membranes and basic optical resonators were fabricated [127] . Although rigorous analysis showed that the membranes are made out of pristine, non graphite containing diamond, no optical signature from NV centers was detected and the structures were not optically active.…”
Section: Photonic Devices From Ion Implanted Membranesmentioning
confidence: 99%
“…Compared to single crystal diamond, however, the optical quality of nano-crystalline diamond films is inferior due to intrinsic scattering and absorption losses. A technique for the production of free-standing, mono-crystalline diamond membranes is graphitisation by high energy ion-implantation producing a sacrificial layer which allows for lifting out a thin membrane [33]. Yet, residual damage due to the ion-implantation causes high optical losses and significant modification of the colour centre (NV − ) luminescence [34].…”
mentioning
confidence: 99%